Peran Service Quality Dan Experiential Marketing Terhadap Customer Loyalty Melalui Customer Satisfaction Coffee Shop Vanko di Surabaya - Mochamad Irfan Octaviananda; Lena Ellitan; Maria Mia Kristianti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This study aims to determine the influence analysis of Service Quality and Experiential Marketing on Customer Loyalty through Customer Satisfaction as mediaition at Coffee Shop Vanko di Surabaya. The Sampling technique uses nonprobality sampling with purposive sampling method, The sample taken were 160 respondents who were consumers of Coffee Shop Vanko in Surabaya. The tool used to retrieve and collect data is in the form of an online questionaire via the Google Chrome. The data analysis technique uses Structural Equations modeling (SEM) using the smart pls program. The results of this study state that Experiential Marketing shows a negative and insignificant effect on Customer Satisfaction, Service Quality has a positive and significant effect on Customer Satisfaction, Customer Satisfaction has a positive and significant effect on Customer Loyalty, Experiential Marketing has a negative and insignificant effect on Customer Loyalty, Service Quality has a positive and significant effect on Customer Loyalty, Customer Satisfaction can mediate the effect of Experiential Marketing on Customer Loyalty, Customer Satisfaction can mediate the effect of Service Quality on Customer Loyalty.